Respiratory functional status after conventional and minimally invasive aortic valve replacement surgery – a propensity score analysis - Stoliński, Jarosław; Musiał, Robert; Plicner, Dariusz; Fijorek, Kamil; Mędrzycki, Michał; Andres, Janusz; Kapelak, Bogusław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction: Reports describing respiratory function of patients after conventional or minimally invasive cardiac surgery are infrequent. Aim: To compare pulmonary functional status after conventional (AVR) and after minimally invasive, through right anterior minithoracotomy, aortic valve replacement (RT-AVR). Material and methods: This was an observational analysis of 212 patients scheduled for RT-AVR and 212 for AVR between January 2011 and December 2014 selected using propensity score matching. Respiratory function based on spirometry examinations is presented. Results: Hospital mortality was 1.4% in RT-AVR and 1.9% in AVR (p = 0.777). Predicted mortality (EuroSCORE II) was 3.2 ±1.1% in RT-AVR and 3.1 ±1.6% in AVR (p = 0.298). Mechanical ventilation time in intensive care unit (ICU) was 7.3 ±3.9 h for RT-AVR and 9.6 ±5.5 h for AVR patients (p < 0.001). Seven days and 1 month after surgery, the reduction of spirometry functional tests was greater in the AVR group than in the RT-AVR group (p < 0.001). Three months after surgery, all spirometry parameters were still reduced and had not returned to preoperative values in both RT-AVR and AVR groups. However, the difference in spirometry values was no longer statistically significant between RT-AVR and AVR groups. Presence of chronic obstructive pulmonary disease and conventional AVR surgical technique were associated with lower values of spirometry parameters after surgery in linear median regression. Conclusions : Respiratory function based on spirometry examinations was less impaired after minimally invasive RT-AVR surgery in comparison to conventional AVR surgery through median sternotomy.